Models and Tools for Investigating Eosinophilic Esophagitis at the Bench - Uchida, Amiko M.; Ro, Gabrielle; Garber, John J.; Peterson, Kathryn A.; Round, June L. (Frontiers in Immunology, 2022)
Eosinophilic esophagitis (EoE) is an increasingly common food allergy disease of the esophagus that received its medical designation code in 2008. Despite this recency, great strides have been made in the understanding of EoE pathophysiology and type 2 immunity through basic and translational scientific investigations conducted at the bench. These advances have been critical to our understanding of disease mechanisms and generating new hypotheses, however, there currently is only one very recently approved FDA-approved therapy for EoE, leaving a great deal to be uncovered for patients with this disease. Here we review some of the innovative methods, models and tools that have contributed to the advances in EoE discovery and suggest future directions of investigation to expand upon this foundation.